Epstein-Barr Virus Neurologic Complications - J. Gordon Millichap (Pediatric Neurology Briefs Publishers, 2015)
Investigators at the Karol Marcinkowski University of Medical Sciences, Poznan, Poland, analyzed the records of 194 children diagnosed with Epstein-Barr virus infection and having the viral capsid antigen IgM antibody.